Historical Trends in Sexual Activity and Sexual Health in France (1992–2023): A Gendered Perspective - Nathalie Bajos; Michel Bozon; Rim Bellamine; Armelle Andro (Perspectives on Sexual and Reproductive Health, 2026)
ABSTRACT Objective To analyze historical gender trends in sexual indicators in France over a period of three decades. Methods We used data from three national probability surveys on sexual behaviors in France conducted in 1992 ( N = 20,055), 2006 ( N = 12,364), and 2023 ( N = 19,015) to compare sexual indicators among men and women aged 18–69 years. Results The median age at first sexual intercourse has increased since the late 2010s, reaching 18.2 years for women and 17.7 years for men in 2023. The average number of lifetime sexual partners for those who have already had a sexual partner increased from 3.4 in 1992, to 4.5 in 2006, to 8.0 in 2023 for women and from 11.2 in 1992, to 11.9 in 2006, and to 16.6 in 2023 for men. Meeting sexual partners online has become widespread, with 44% of women and 48% of men aged 18–29 doing so in 2023. The prevalence of same‐sex partners also increased, from 3% in 1992 to 4% in 2006 to 10% in 2023 for women and from 4% in 1992 and 2006 to 9% in 2023 for men. Sexual activity in the past year and the frequency of sexual intercourse in the last 4 weeks decreased among single respondents since the 2000s. Meanwhile, having multiple partners and having masturbated increased, especially among women. Conclusion These changes, which reflect increases in women's sexual agency and may partly be attributed to the digital revolution, need to be considered when tailoring public health messages to these new realities.